2021
DOI: 10.1088/1757-899x/1047/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Reliability indexes of vibrating platforms for compaction of construction mixtures

Abstract: In the article of experimental research and a particularly important prerequisite is to establish the required values with the least error, because the reliability of the information obtained from the processing of experiments is key to determine the true value of a parameter. According to the results of the study, data were obtained on the actual operating time for failure of the elements of the vibrating platforms VB-10V. The research identified the main prefabricated units and parts that failed: motor, gear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The studies carried out [2,7,[10][11][12][13][14][15][16][17][18][19] identified the main prefabricated units and parts that fail: engine, gearbox, synchronizer, vibration exciter, propeller shafts, couplings, photographs of such failures are shown in Fig. 7.17.…”
Section: Research Of Indicators Of Reliability Of Technical Systemsmentioning
confidence: 99%
“…The studies carried out [2,7,[10][11][12][13][14][15][16][17][18][19] identified the main prefabricated units and parts that fail: engine, gearbox, synchronizer, vibration exciter, propeller shafts, couplings, photographs of such failures are shown in Fig. 7.17.…”
Section: Research Of Indicators Of Reliability Of Technical Systemsmentioning
confidence: 99%
“…The problem of moving agricultural materials on the working surfaces of the separators was solved, provided that such materials are discrete solids; tasks were solved of layer-by-layer processes and self-sorting, clogging and cleaning of sieve openings, sifting of seeds through sieve openings. In the works [5; 6] the dependences of the quality of separation of a flat sieve on the main parameters are obtained: kinematic mode of operation and angle of inclination of the sieve to the horizon, angle of oscillation, shape and location of holes, sieve sizes and specific loading, humidity and clogging of grain material [7]. Kalivoda J.…”
Section: Introductionmentioning
confidence: 99%